Reducing bioavailability of heavy metals in contaminated soil and uptake by maize using organic-inorganic mixed fertilizer. (December 2020) - Wang, Qingqing; Huang, Qing; Guo, Genmao; Qin, Jiemin; Luo, Junyi; Zhu, Zhiqiang; Hong, Yi; Xu, Yuxin; Hu, Shan; Hu, Wen; Yang, Chen; Wang, Junfeng
Abstract: Heavy metals in soil are harmful to human health via the food chain, but little is known about the mechanism of reducing bioavailability of Cd or Pb to maize ( Zea mays L.) by applying complex amendments to soil. A field experiment was conducted at a tropical site in Hainan Province, China, that had been subjected to soil pollution by Cd and Pb from past mining activities. There were ten treatment groups comprising a mixture of biochar, hydroxyapatite (HAP), manure, and plant ash in varying proportions and at three different rates. Compared with untreated soil, all treatments increased pH by 2–3 units in bulk soil or 1–2 units in rhizosphere soil. For all amendments, the concentration of Cd in all parts of maize plants was decreased compared with unamended soil, but this effect was much smaller for Pb. The greatest effect was found with a mixture containing the ratio of HAP:manure:biochar:plant ash as 6:4:2:1 when applied at 20.1 t ha −1 . The dominant microbial group in contaminated soil was Proteobacteria. There is evidence that this group can immobilize Cd by mechanisms that include biosorption and bioprecipitation. It was concluded that the mixed amendments containing biochar, HAP, manure, and plant ash can be useful in decreasing Cd uptake by maize. The amendment in this study likely operates through a combination of soil chemical changes and by influencing the soil-microbe-plant interaction. Graphical abstract: Image 1 Highlights: Soil pH and crop yield were significantly improved in the A1 treatment. The bioavailability of Cd was remarkably decreased with the application of A1 amendment. The microbial community was shaped by additions with increases in groups likely to immobilize Cd.